TAHAP PENGAMALAN BUDAYA KUALITI DALAM KALANGAN GURU-GURU SEKOLAH RENDAH - Raya, Zuhaida; Abd Razzaq, Abdul Rasid (Online Journal for TVET Practitioners, 2018)
This descriptive study aims to investigate the practice of quality culture among primary schools teachers in the Tiram Zone Pasir Gudang District. The quality culture dimensions studied in this study are customer management, value sharing, continuous improvement, quality training, comprehensive engagement, communication climate and teamwork. Quality culture dimensions are based on the study of Patimah Ibrahim (2002). The data were collected via questionnaire and analyzed using the Statistical Package For Social Science (SPSS) program to obtain the frequency, mean, and standard deviation. The results of the pilot study found that the Alpha Cronbach’s reliability (Î±) quality culture dimension was 0.9003, according to what Nunnally (1978) suggested that alpha values greater than 0.70 were consistent for each dimension used. A total of 170 teachers were randomly selected as stratified respondents. Overall, the findings show that quality culture practices in the schools studied are high. The findings show that team work dimensions and communication climate show the most dominant practice in the study school. This study has important implications for teachers in general to better understand the dimensions of quality culture practiced and to know their impact on school-age disabilities. Through this study, it is hoped that it will contribute to the transition or shift of the mind among educators in order to improve the performance and quality of education in Malaysia.